2020
DOI: 10.1002/jmri.27322
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging for Quantitative Assessment of Anterior Cruciate Ligament Injury Grades and Graft

Abstract: Background As the need for quantitative assessment of anterior cruciate ligament (ACL) injuries and ACL graft increases, diffusion tensor imaging (DTI) becomes a more valuable measuring tool. However, DTI changes in differing injury grades of ACL and longitudinal graft remain unclear. Purpose To investigate the diagnostic performance of DTI in quantitatively assessing ACL injury severity and the development of ACL grafts within 6 months of surgery. Study Type A cohort study. Subjects Thirty‐five patients diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Dyck et al demonstrated the feasibility and reliability of DTI for the visualization and quantitative evaluation of the ACL graft using a clinical 3T system 77 . DTI provided objective biomarkers to assess graft healing following ACL reconstruction to guide the time of return to sports 77–79 . The zonal‐dependent DTI metrics (FA, MD, axial, and transversal diffusivity) of the porcine meniscus have been recently reported using a 3D DW‐SE sequence 80 .…”
Section: Musculoskeletal Applications Of Quantitative Diffusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dyck et al demonstrated the feasibility and reliability of DTI for the visualization and quantitative evaluation of the ACL graft using a clinical 3T system 77 . DTI provided objective biomarkers to assess graft healing following ACL reconstruction to guide the time of return to sports 77–79 . The zonal‐dependent DTI metrics (FA, MD, axial, and transversal diffusivity) of the porcine meniscus have been recently reported using a 3D DW‐SE sequence 80 .…”
Section: Musculoskeletal Applications Of Quantitative Diffusionmentioning
confidence: 99%
“…77 DTI provided objective biomarkers to assess graft healing following ACL reconstruction to guide the time of return to sports. [77][78][79] The zonal-dependent DTI metrics (FA, MD, axial, and transversal diffusivity) of the porcine meniscus have been recently reported using a 3D DW-SE sequence. 80 The complex collagen fiber architecture of the entire meniscus can be resolved by diffusion tractography.…”
Section: Ligaments Tendons and Meniscimentioning
confidence: 99%
“…Some studies have verified that DTI can be used to quantitatively evaluate the ACL injury grade and the development of ACL grafts in vivo using a clinical 3.0-Tesla (3.0T) scanner. 14,15 To the best of our knowledge, however, no study has evaluated the fibrous microstructure of the ACL using 7.0T MRI.…”
Section: Introductionmentioning
confidence: 99%
“…The study “Diffusion Tensor Imaging for Quantitative Assessment of Anterior Cruciate Ligament Injury Grades and Graft” by Liu et al, 4 published in this issue of the Journal of Magnetic Resonance Imaging , evaluates two promising clinical applications of DTI. First, DTI‐derived measures are shown for the diagnostic assessment of ACL injury grades, and second, the longitudinal assessment of ACL grafts in patients having undergone reconstructive surgery is shown with DTI.…”
mentioning
confidence: 99%